Christian Ethics Promoting Factors of the Traditional Model of the Family, With Special Regard to Canon Law - Bielecki, Marek (Demographic Challenges in Central Europe: Legal and Family Policy Response, 2024)
This chapter presents the assumptions of Christian ethics relating to the issue of promoting the traditional family model. I analyse the doctrine of particular churches and religious associations, considering both theological issues and the internal law institutions of various confessional entities. Given that the community of Christian churches is extremely broad, the scope of research has been narrowed to only a selection of entities: in light of the number of followers, the considerations mainly cover the teachings of the Roman Catholic Church; however, I also examine the position of selected Protestant and Orthodox communities. The internal law of particular churches and religious associations is characterised by a high level of diversity, and some of the confessions have structured sets of legal regulations. In the case of the Catholic Church, the term ‘canon law’ is used to describe internal law, which was systematised in 1983 as the Code of Canon Law. The internal norms adopted by the individual churches and religious associations reflect their religious doctrine and constitute their practical dimension.Keywords: Christian ethics, internal law, church, religious association, family